Cover Image. (14th August 2020) - Li, Gang; Mai, Guangming; Zhang, Jiejun; Lin, Qiang; Ni, Guangyan; Tan, Yehui; Huang, Liangmin; Zou, Dinghui
Abstract : The cover image is based on the Original Article Algal density alleviates the elevated CO2 ‐caused reduction on growth of Porphyra haitanensis (Bangiales, Rhodophyta), a species farmed in China by Gang Li et https://doi.org/10.1111/are.14735 .